Transient cavity dynamics and divergence from the Stokes–Einstein equation in organic aerosol. Issue 11 (24th February 2020) - Song, Young-Chul; Ingram, Stephen; Arbon, Robert E.; Topping, David O.; Glowacki, David R.; Reid, Jonathan P.
Abstract : The failure of the Stokes–Einstein relation is assessed in aerosol measurements and molecular dynamics simulations. Abstract : The diffusion of small molecules through viscous matrices formed by large organic molecules is important across a range of domains, including pharmaceutical science, materials chemistry, and atmospheric science, impacting on, for example, the formation of amorphous and crystalline phases. Here we report significant breakdowns in the Stokes–Einstein (SE) equation from measurements of the diffusion of water (spanning 5 decades) and viscosity (spanning 12 decades) in saccharide aerosol droplets. Molecular dynamics simulations show water diffusion is not continuous, but proceeds by discrete hops between transient cavities that arise and dissipate as a result of dynamical fluctuations within the saccharide lattice. The ratio of transient cavity volume to solvent volume increases with size of molecules making up the lattice, increasing divergence from SE predictions. This improved mechanistic understanding of diffusion in viscous matrices explains, for example, why organic compounds equilibrate according to SE predictions and water equilibrates more rapidly in aerosols.